Bovine central nervous system development - Ferreira, Amanda O.; Vasconcelos, Bruno G.; Favaron, Phelipe O.; Santos, Amilton C.; Leandro, Rafael M.; Pereira, Flávia T.V. [UNESP]; Maria, Durvanei A.; Miglino, Maria Angélica (FapUNIFESP (SciELO), 2018)
Central nervous system (CNS) development researches are extremely important to the most common congenital disorders and organogenesis comprehension. However, few studies show the entire developmental process during the critical period. Present research can provide data to new researches related to normal development and abnormalities and changes that occur along the CNS organogenesis, especially nowadays with the need for preliminary studies in animal models, which could be used for experimental research on the influence of viruses, such as the influence of Zika virus on the development of the neural system and its correlation with microcephaly in human newborns. Then, present study describes CNS organogenesis in cattle according to microscopic and macroscopic aspects, identifying structures and correlating to gestational period. Fourteen embryos and nine bovine fetuses at different ages were collected and analyzed. All individuals were measured in order to detect the gestational period. Bovine embryo at 17 days age has its neural tube, cranial neuropore, caudal neuropore and somites developed. After 24 days of development, were observed in cranial part of neural tube five encephalic vesicles denominated: telencephalon, diencephalon, mesencephalon, metencephalon and myelencephalon. In addition, the caudal part of neural tube was identified with the primitive spinal cord. The primordial CNS differentiation occurred from 90 to 110 days. The five encephalic vesicles, primordial spinal cord and the cavities: third ventricule, mesencephalic aqueduct, fourth ventricle and central canal in spinal cord were observed. With 90 days, the main structures were identified: (1) cerebral hemispheres, corpus callosum and fornix, of the telencephalon; (2) interthalamic adhesion, thalamus, hypothalamus and epythalamus (glandula pinealis), of the diencephalon; (3) cerebral peduncles and quadruplets bodies, of the mesencephalon; (4) pons and cerebellum, of the metencephalon; (5) medulla oblongata or bulb, of the myelencephalon; and (6) spinal cord, of the primitive spinal cord. After 110 days of gestation, the five encephalic vesicles and its structures were completely developed. It was noted the presence of the spinal cord with the cervicothoracic and lumbossacral intumescences. In summary, the results describes the formation of the neural tube from the neural plate of the ectoderm, the encephalic vesicles derived from the neural tube and subsequent structural and cavities subdivisions, thus representing the complete embryology of the central nervous system.
Keywords: Bovine central nervous system; CNS; Encephalic vesicles; Encephalon; Ontogeny; Spinal cord